The Role of Attitude in Mediating the Effect of Service Quality on Tax Compliance Among Taxpayers at the Lubuk Pakam Local Tax Office - Makrufan Nasution, Umriza; Erwansyah; B, Mesra (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the mediating role of attitude in the effect of service quality on tax compliance among individual taxpayers at the Lubuk Pakam Primary Tax Office. This study employs a quantitative approach using a survey method. The research sample consisted of 395 respondents selected using probability sampling based on the Slovin formula. Data were collected via a questionnaire using a Likert scale and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0. The results indicate that service quality has a positive and significant effect on taxpayers’ attitudes. Service quality also has a positive and significant effect on tax compliance. Furthermore, taxpayers’ attitudes have a positive and significant effect on tax compliance. The results of the indirect effect test indicate that attitudes significantly mediate the effect of service quality on tax compliance. These findings indicate that improving tax service quality not only has a direct impact on taxpayer compliance but also works by fostering positive taxpayer attitudes. Thus, enhancing service quality is a crucial strategy for improving tax compliance by changing taxpayer attitudes at the Lubuk Pakam Primary Tax Office.